Pelayanan Publik Pada Dinas Kependudukan dan Pencatatan Sipil di Kabupaten Lamongan Dalam Perspektif Fikih Siyasah - Nur Lailatul Musyafaah; Arif Wijaya (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2020)
This article discusses public services at the Population and Civil Registration Service (Dispendukcapil) Lamongan according to Fiqh Siyasah. This research is field research and is qualitative in nature. Data were collected through observation, interviews, and documentation. The collected data were analyzed by the deductive method. The result of the research shows that public services in the Dispendukcapil Lamongan are related to administrative services, which include population services (KTP, KK, Transfer Certificate) and civil registration services (birth certificates, death certificates, marriage certificates, divorce certificates, child validation certificates). Even though the Dispendukcapil Lamongan has made efforts to improve services, there are still complaints from the public in several services, both from service attitudes and facilities, including in the queuing system and waiting room facilities. In the fiqh siyasah perspective, the public services provided by the Dispendukcapil Lamongan are part of the fiqh siyasah idariyyah (administrative management fiqh). In serving the people, a state employee must be trustworthy, honest, and fair. The service must be based on benefit as the rule of tasharruf al-imam ala al-raiyyah manut bi al mashlahah (Public service must be based on maslahat). Based on this, it is hoped that the Dispendukcapil Lamongan will further improve the quality of services, facilities, and infrastructure. Abstrak: Artikel ini membahas tentang Pelayanan Publik pada Dinas Kependudukan dan Pencatatan Sipil (Dispendukcapil) Lamongan menurut Fikih Siyasah. Penelitian ini adalah Penelitian lapangan dan bersifat kualitatif. Data dikumpulkan melalui observasi, wawancara dan dokumentasi. Data yang terkumpul dianalisis dengan metode deduktif. Hasil penelitian adalah pelayanan publik di Dispendukcapil Lamongan adalah berkaitan dengan pelayanan administrasi yaitu meliputi pelayanan kependudukan (KTP, KK, Surat Keterangan Pindah) dan pelayanan pencatatan sipil (Akta Kelahiran, Akta Kematian, Akta Perkawinan, Akta Perceraian, Akta pengesahan anak). Meskipun Dispendukcapil Kabupaten Lamongan telah berusaha meningkatkan pelayanan, masih terdapat keluhan masyarakat dalam beberapa pelayanan baik dari sikap pelayanan maupun fasilitas, di antaranya dalam sistem antrian dan fasilitas ruang tunggu. Dalam perspektif fikih siyasah, pelayanan publik yang diberikan Dispendukcapil Kabupaten Lamongan merupakan bagian dari fikih siyasah idariyyah (fikih pengelolaan administrasi). Dalam melayani rakyat, seorang pegawai negara harus amanah, jujur dan adil. Pelayanan tersebut harus didasarkan pada kemaslahatan sebagaimana kaidah tasharruf al-imam ala al-raiyyah manut bi al mashlahah (Pelayanan publik harus didasarkan pada maslahat). Berdasarkan hal tersebut, diharapkan DIspendukcapil Lamongan semakin meningkatkan kualitas pelayanan, sarana dan prasarana.